Satisfaction Level of Clients in DMPA Injectible Contraceptive Service at Baumata Health Care, Kupang District - Friska Rosiana Atolo; Tadeus A. L. Regaletha; Rina Waty Sirait (Media Kesehatan Masyarakat, 2022)
Satisfaction is a form of one's feelings after experiencing service quality that has met expectations. Health services, especially family planning, is expected to meet the needs of acceptors. However, there are complaints from acceptors related to the service of injectable contraceptive received. These complaints are related to the comfortability of the waiting room, the condition of the family planning room that is still not neatly arranged, and the lack of family planning equipment. The measurement of acceptor satisfaction needs to be carried out regularly, accurately and continuously through a satisfaction survey. This study aims to determine the level of acceptor satisfaction with Depo-Medroxyprogesterone Acetate (DMPA) injection family planning at Baumata Health Center, Kupang Regency. The study was a survey with a quantitative approach. This study had a population of 74 people. A sample of 43 people were selected using proportional random sampling technique. The data were analyzed using the Importance Performance Analysis (IPA) method. The results showed that acceptors were satisfied for the tangible dimension (88.4%), and very satisfied for the dimension of reliability (95.5%), responsiveness (95.3%), assurance (94.5%) and empathy (96.5%). The health center needs to improve the service quality of injectable contraceptives by ensuring the availability of related devices, timeliness in the service provision, and complete preparation of the injectable birth control equipment.